The pattern of non-COVID-19 paediatric admissions in Malaysia teaching hospitals: before and during the COVID-19 pandemic with Movement Control Order - Muhammad, SA; Taib, Fahisham; Mohd Rawi, R; Ariffin, WN; Anuar, Muhamad Azamin; Abu Bakar, Asrar; Abd Hamid, Intan Juliana; Syed Abd. Hamid, Syed Abdul Khaliq (Faculty of Medicine, University Malaya, 2022)
To study the characteristics of paediatric patients admitted to two non-COVID-19 teaching hospitals before and during the implementation of the Movement Control Order (MCO) in Malaysia. The retrospective study was performed in two phases (before MCO between February to March 2020, and during MCO lockdown between March to April 2020) in two teaching hospitals on the East Coast of Peninsular Malaysia. Hospitalized children <18 years were included and those coming for elective procedures or oncology treatment were excluded. The clinical data were retrieved from both hospitals’ admission records. There was a total of 496 and 191 admissions to two teaching hospitals on the East Coast of Peninsular Malaysia, respectively. A significant reduction in the number of non-COVID-19 hospital admissions was seen in both hospitals. For Hospital Universiti Sains Malaysia, the daily hospital admissions were reduced with a mean of 10 (before MCO) to 7 (during MCO) admissions/day (95% CI 1.54,7.54, p=0.001). In Sultan Ahmad Shah Medical Centre, a reduction in hospital admission was seen from 5 (before MCO) to 3 (during MCO) admissions/day (95% CI 0.61, 3.15, p=0.005). Our study observed a general drop in non-COVID-related respiratory illnesses and infectious disease cases during the MCO period. There were significant differences in neurological (p=0.029) and accident (p = 0.001) cases admissions observed between the two periods. Public health social distancing has indirectly reduced the non-COVID-19 related cases in the hospital settings with an increase in accidental injuries among the children during the MCO period.